The mechanism of cadmium removal from aqueous solution by nonmetabolizing free and immobilized live biomass of Rhizopus oligosporus - Aloysius, R.; Karim, M.I.A.; Ariff, A.B. (Kluwer Academic Publishers, 1999)
A preliminary study on the removal of cadmium by nonmetabolizing live biomass of Rhizopus oligosporus from aqueous solution is presented. The equilibrium of the process was in all cases well described by the Langmuir sorption isotherm, suggesting that the process was a chemical, equilibrated and saturable mechanism which reflected the predominantly site-specific mechanism on the cell surface. A curve of Scatchard transformation plots reflected the covalent nature of Cd2+ adsorption by the cells. The maximum cadmium uptake capacities were 34.25 mg/g for immobilized cells and 17.09 mg/g for free cells. Some factorial experiments in shake flasks were performed in order to investigate the effect of different initial cadmium concentrations and biomass concentrations on the equilibrium. Experimental results showed a reverse trend of the influence of the immobilized and free biomass concentration on the cadmium specific uptake capacity. The immobilized cells had a higher specific cadmium uptake capacity with increasing biomass concentrations compared to free cells. In a bioreactor, the cadmium uptake capacity of immobilized cells (q(max) = 30.1-37.5 mg/g) was similar to that observed in shake flask experiments (q(max) = 34.25 mg/g) whereas with free cells the bioreactor q(max) of 4.8-13.0 mg/g; was much lower than in shake flasks (q(max) = 17.09 mg/g), suggesting that cadmium biosorption by immobilized cells of R. oligosporus might be further improved in bigger reactors. EDAX and transmission electron microscopic experiments on the fungal biomass indicated that the presence of Cd2+ sequestrated to the cell wall was due to bioadsorption.